Influence of neurodynamic properties on the choice of coping strategies in qualified athletes - Svitlana Fedorchuk; Olena Lysenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: evaluation of the influence of neurodynamic properties on the formation of coping strategies with stress in qualified athletes. Material & Methods: study involved 43 high-class athletes (MS, MSIG, HMS) at the age of 14-29 years (kind of sport - kayaking and canoeing). To determine the neurodynamic properties of athletes, the Diagnostic Complex "Diagnostic-1" was used to determine the strategies of stress-overcoming behavior-the "Questionnaire of Ways of Coping Questionnaire" by R. Lazarus and S. Folkman. The study used the final score of the test of competitive personal anxiety. Results: surveyed athletes identified the prevalence of such coping strategies as "Self-control", "Seeking social support", "Taking responsibility", "Problem solving planning" and "Positive revaluation". The interrelationships of coping strategies with indices of neurodynamic properties-the strength and dynamism of nervous processes, the rate of complex selection reaction. Conclusions: specific psychophysiological markers of such coping strategies as "Search for social support", "Taking responsibility" and "Escape-avoidance", one can consider indicators of the strength and dynamics of nervous processes, the speed of a complex selection reaction. The preference for non-constructive coping strategies for athletes was associated with an increase in the run-up time (the time for reaching the minimum exposure of the signals in the feedback mode).